Pengaruh Content Marketing dan Electronic Word Of Mouth (E-Wom) Terhadap Keputusan Pembelian Makanan dan Minuman Pengikut Akun Instagram @Surabaya_Foodies di Kota Surabaya - Ariyani Dewi Safitri; Ugy Soebiantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the effect of Content Marketing and Electronic Word of Mouth on Purchase Decision of buy food and beverage followers of the instahram account @surabaya_foodies. The research method used is a quantitative method. The sampling method used is non-probability sampling with pirposive sampling method consist of 108 respondents. Partial Least Square (PLS) is used to analyze the data with SmartPLS 3.0 program. Partial Least Square (PLS) analysis consist of 3 steps. First step is Outer Model analyzation (validity & reability variable test), then Inner Model analysis and Hypothesis Test. The result of this research shows that (1) Content Marketing has significant and positive effect on Purchase Decision and (2) Electronic Word of Mouth (e -WOM) has significant and positive effect on Purchase Decision.